Analysis of trends in development of China's industry - Thosaporn Khetkaewsomboon; Tang, John C.S.; Donyaprueth Krairit; Zimmermann, Willi; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
The IT revolution has changed in China's computer industry. The country has now appeared as both a large market size and a leading producer of world's computer hardware. The domestic PC market grew from less than one million units in 1995 to more than 16.8 millions unit in 2005.China is the world's second-largest PC market in Asia-Pacific region after Japan. While in export market, the industry has gone from virtually non-existent in 1983 and provided with its accession to the World Trade Organization (WTO) in 2001, Chinese computer hardware production has tripled while output in the other countries such as US, Japan, Taiwan and Singapore has declined. In 2004, China became the largest computer hardware producer in the world with US$81 billion in output of which most productions and exports dominated by Taiwanese firms. Taiwanese firms have strongly influence on development of China's PC industry. Most of China's notebook PC is made by Taiwanese firms which also manufacture computer components and peripherals for desktop computers assembled by the Chinese computer markets. This research paper is using Michael E. Porter diamond model "competitive advantage of nation" to examine factors contribute extraordinary growth and rapid development of China's computer industry focusing on personal computer (PC) market and generic strategy model to analyze business strategies for China's market. This includes the roles played by government, foreign and domestic PC vendors. The study includes impacts of Chinese government policies that promoted computer production and use in China and the degree to which China's computer industry is linked with foreign firms, especially from Taiwanese firms for production capacity, technical know-how, and capital investment. Lastly, this research also include future China's PC market trend.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Business
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: Computer industry -- China